2019
DOI: 10.1016/j.nima.2019.162420
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site event discrimination in large liquid scintillation detectors

Abstract: Simulation studies have been carried out to explore the ability to discriminate between single-site and multi-site energy depositions in large scale liquid scintillation detectors. A robust approach has been found that is predicted to lead to a significant statistical separation for a large variety of event classes, providing a powerful tool to discriminate against backgrounds and break important degeneracies in signal extraction. This has particularly relevant implications for liquid scintillator searches for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These efforts include a precision measurement of attenuation at long distances, demonstration of material compatibility with detector components, and accurate costs and production capabilities. Examples include WbLS development at BNL [29], compatibility studies at UC Davis, characterization and optimization with the CHESS detector at UC Berkeley and LBNL [23,30], fast photon sensor development at Chicago and Iowa State [31], spectral photon sorting at Penn [26], development of reconstruction and particle identification algorithms [32][33][34][35][36][37][38][39][40], and potential nanoparticle loading in NuDot at MIT [41]. A practical purification system is being developed at UC Davis [42].…”
Section: Water-based Liquid Scintillatormentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts include a precision measurement of attenuation at long distances, demonstration of material compatibility with detector components, and accurate costs and production capabilities. Examples include WbLS development at BNL [29], compatibility studies at UC Davis, characterization and optimization with the CHESS detector at UC Berkeley and LBNL [23,30], fast photon sensor development at Chicago and Iowa State [31], spectral photon sorting at Penn [26], development of reconstruction and particle identification algorithms [32][33][34][35][36][37][38][39][40], and potential nanoparticle loading in NuDot at MIT [41]. A practical purification system is being developed at UC Davis [42].…”
Section: Water-based Liquid Scintillatormentioning
confidence: 99%
“…This includes possibilities for particle identification at energies as low as a few MeV based on topological information. For example it is now possible to distinguish point-like events from multi-site events in liquid scintillator [35] using various techniques, including likelihood-based pulse shape discrimination methods [36]. Figure 3 shows an example of the separation of electrons from gammas, critical for separation of neutrino scatters, which produce electrons, from common gamma emitters in the uranium and thorium decay chains.…”
Section: Reconstruction Techniquesmentioning
confidence: 99%
“…Additionally, both the improved timing and pixelation of LAPPDs lead to enhanced vertex reconstruction in larger detectors. This leads to improved PID, such as distinguishing e − events from e + , γ , or α particles [44]. Studies for the ANNIE detector have shown that the introduction of five LAPPDs (to a baseline design of 125 PMTs) enhances vertex resolution from about Fig.…”
Section: Lappdsmentioning
confidence: 99%
“…Substantial work has been dedicated to realizing this concept, both experimentally (218)(219)(220)(221)(222) and in the development of new analysis tools to leverage and enhance this simultaneous detection for large detectors (223)(224)(225)(226)(227)(228)(229).…”
Section: Real-time Detectorsmentioning
confidence: 99%